(3GdLPhQ GdJGQjNjI ddbGfhf GdQheGfj (B: s (3OQGSI ai adSaI GdbGfhf h JGQjNg (B/ s - (3eMeO eUWai CMeO UbQs; (3eMehO GdSbGs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2019)
(3HYO GSJYQGVfG ddbGfhf GdQheGfi h eQGMd JWhQg h Cge GdYhGed GdeDKQI ajg HGdEVGaI Edi fXQI GdQheGf Edi GdCLGfH h JWhQgG NdUfG Edi YOI fJGFL CgegG Cf GdbGfhf egeG cGfJ bhGYOg UdHI h LGeOI EdG CfgG JNVY dSfI GdRef ai GdJWhQ h Cf GdYOGdI h GdeSGhGI ef Cge GdCSHGH GdJi Jcad ddbhGfjf GdESJeQGQ h GdESJbQGQ ceG GfJgjfG Edi YOI JhUjGJ JJeKd ai VQhQI eQGYGI GdYOGdI YfO Sf eNJda GdbhGfjf h VQhQI LYd GdbhGYO GdbGfhfjI eQfI eY eQGYGI cGaI GdLhGfH GdELJeGYjI h GdEfSGfjI h GdEbJUGOjI YfO Sf Ci bGfhf ef GdbhGfjf eY VQhQI OQGSI GdehGO GdadSajI dWdHI cdjGJ GdMbhb s
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe adSaI GdbGfhf hJGQjNg (B2019.s
(3HHdjhLQGajG(B: (3UaMGJ (B267-276.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3LSJfjGfs -- -565; (3cQGcdGs; (3GdbGfhf GdQheGfjs; (3GdYUQ GdYdejs; (3bGfhf GdCdhGM GdGKfj YTQs; (3GdbGfhf GdHQjJhQis; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3adSaI GdbGfhfs